Evaluated Daily Intake and Health Risk Assessment of Some Toxic Heavy Metals in Baby Powder for Various Brands Marketed in Benghazi, Libya - M. Yaghi , Maysson; A. Alhursh , Zainab; A. EL Shawish , Afia (Libyan Journal of Public Health Practices, 2026)
Baby powder is a popular baby care product that is used to keep the baby's skin dry and prevent the development of dermatological conditions. Recently, there has been growing scientific interest about the presence of toxic heavy metals in baby powder that has led to concerns regarding its potential effects on human health and the environment. In this study, sixteen baby powder brands that are widely in demand at various pharmacies located in Benghazi were collected in November 2024. First, metals, including aluminium, cadmium, chromium, copper, lead, and nickel, were analyzed in the selected samples using atomic absorption spectrophotometry after a suitable digestion process, followed by the evaluation of health risks across the age groups for infants by the calculation of the chronic daily intake (CDI) that is measured in mg/kg/day from dermal absorption, target hazard quotient (THQ), hazard index (HI), and carcinogenic risk (CR). In regard to heavy metal toxicity, Al, Pb, Ni, Cu, Cr and Cd in all examined baby powders were above the permissible threshold established by the United States Food and Drug Administration (FDA). The findings indicate that periodic monitoring and quality control of baby powders is necessary to meet safety standards and protect infant health. Further, the result of non-carcinogenic and carcinogenic risk estimates was lower than the limits of safe risk (HQ and HI > 1 and cancer risk CR < 1 × 10⁻⁴), suggesting no potential lifetime cancer risk.